Teacher strategies in building islamic value-based competencies and optimizing technology in the digital age - Utami, Fahra; Anggraini, Wulan; Ikra Negara, Amanda; Abdurrahmansyah, Abdurrahmansyah; Alya Salsabila binti Ismail, Nur (EduStream: Jurnal Pendidikan Dasar, 2025)
This study aims to explore the strategies used by Madrasah Ibtidaiyah teachers in developing students’ competencies based on Islamic values while optimizing the use of technology in the digital age. Teachers have an important role in integrating technology in learning without ignoring Islamic values. This research uses descriptive qualitative methods with literature study and interviews to explore competency development strategies and technology utilization. The literature study involved tracing various scientific sources, while interviews were conducted with teachers to understand the implementation of learning strategies and the challenges faced. The results show that to overcome the limitations of teachers’ infrastructure and technology skills, solutions that can be implemented include the development of a more stable and affordable community-based internet network and the utilization of portable learning devices such as mini routers or satellite-based hotspots. In addition, online and offline-based technology training is effective in improving teachers’ skills, especially in areas with limited internet access. Teachers are also encouraged to create simple digital learning media such as offline-based apps or PowerPoint-based interactive media that can be disseminated via USB devices or memory cards. Although technology has been applied in learning, challenges such as limited infrastructure, teacher readiness, and learners’ digital literacy still need to be overcome. The study concludes that although technology enhances learning effectiveness, its successful integration requires adequate infrastructure, teacher training, and support to ensure Islamic values are preserved.